Impacts of the MHC class I-like XNC10 and innate-like T cells on tumor tolerance and rejection in the amphibian Xenopus. (1st June 2019) - Banach, Maureen; Edholm, Eva-Stina; Gonzalez, Xavier; Benraiss, Abdellatif; Robert, Jacques
Abstract: The conditions that lead to antitumor or protumor functions of natural killer T (NKT) cells against mammalian tumors are only partially understood. Therefore, insights into the evolutionary conservation of NKT and their analogs—innate-like T (iT) cells—may reveal factors that contribute to tumor eradication. As such, we investigated the amphibian Xenopus laevis iT cells and interacting MHC class I-like ( XNC or mhc1b.L ) genes against ff-2 thymic lymphoid tumors. Upon ff-2 intraperitoneal transplantation into syngeneic tadpoles, two iT cell subsets iVα6 and iVα22, characterized by an invariant T-cell receptor α chain rearrangement ( Vα6-Jα1.43 and Vα22-Jα1.32 respectively), were recruited to the peritoneum, concomitant with a decreased level of these transcripts in the spleen and thymus. To address the hypothesize that different iT cell subsets have distinct, possibly opposing, roles upon ff-2 tumor challenge, we determined whether ff-2 tumor growth could be manipulated by impairing Vα6 iT cells or by deleting their restricting element, the XNC gene, XNC10 ( mhc1b10.1.L ), on ff-2 tumors. Accordingly, the in vivo depletion of Vα6 iT cells using XNC10-tetramers enhanced tumor growth, indicating Vα6 iT cell-mediated antitumor activities. However, XNC10- deficient transgenic tadpoles that also lack Vα6 iT cells were resistant to ff-2 tumors, uncovering a potential new function of XNC10 besides Vα6 iT cell development. Furthermore, the CRISPR/Cas9-mediated knockout of XNC10 in ff-2 tumors broke the immune tolerance. Together, our findings demonstrate the relevance of XNC10/iT cell axis in controlling Xenopus tumor tolerance or rejection. Abstract : Using genetic loss of function and tetramer technology in a Xenopus tumor immunity model, we provide evidence for the critical functions of innate-like T cells and the CD1d functional analog XNC10 in the balance between protumor and antitumor microenvironments.